THE IMPLEMENTATION OF COLLABORATIVE LEARNING IN TEACHING SPEAKING OF ANALYTICAL EXPOSITION TO THE ELEVENTH GRADERS OF SMAN 1 SIDOARJO (RETAIN, 2014)
THE IMPLEMENTATION OF COLLABORATIVE LEARNING IN TEACHING SPEAKING OF ANALYTICAL EXPOSITION TO THE ELEVENTH GRADERS OF SMAN 1 SIDOARJO Dina Nur Elia English Education Department, Language and Arts Faculty, Surabaya State University. Email: dina.elia99@gmail.com Dr. Oikurema Purwati, M.Appl English Education Department, Language and Arts Faculty, Surabaya State University. Abstrak Pembelajaran kemampuan berbicara bahasa Inggris merupakan hal yang penting dalam konteks bahasa Inggris sebagai bahasa asing. Kemampuan berbicara dikategorikan sebagai kemampuan yang produktif. Dimana terjadi proses berpikir di dalammnya. Salah satu tujuan pembelajaran kemampuan berbicara adalah siswa dapat berkomunikasi dengan orang lain melalui komunikasi yang berarti dan berterima. Dalam studi ini, penulis telah mengobservasi seorang guru bahasa Inggris yang telah menerapkan collaborative learning dalam pembelajaran kemampuan berbicara. Guru tersebut telah menciptakan kegiatan yang menarik dalam kegiatan berbicara dimana siswa diminta untuk mempresentasikan sebuah topik yang telah ditentukan oleh guru di depan kelas dengan berkolaborasi . Banyak manfaat yang didapat dari kegiatan tersebut. Penelitian ini dirancang dalam penelitian deskriptif kualitatif. Subject penelitiannya adalah guru dan siswa kelas XII IPA 8 di SMA Negeri 1 Sidoarjo. Instrumen yang digunakan dalam penelitian tersebut adalah catatan lapangan, panduan pertanyaan wawancara, dan traskrip penampilan siswa ketika presentasi di depan kelas. Penerapan metode collaborative learning dalam pembelajaran kemampuan berbicara pada teks analytical exposition telah berhasil menarik siswa dalam kegitan pembelajaran berbicara. Guru tersebut mampu mnerapkan metode tersebut dengan sukses. Langkah-langkah yang diterapkan oleh guru tersebut telah memenuhi kriteria langkah-langkah yang ada pada metode collaborative learning. Para siswa telah menunjukan respon yang baik terhadap metode yang diterapkan oleh guru tersebut. Dalam penentuan hasil penerapan dari collaborative learning tersebut, apakah menunjukan hasil yang baik atau kurang baik tidak hanya dilihat dari respon siswa terhadap penerapan collaborative learning tersebut saja, tetapi juga mengacu pada hasil penampilan siswa dalam mempresentasikan topik yang diberikan oleh guru di depan kelas. Penampilan siswa mampu mewakili pemahaman siswa dalam kaitannya dengan materi yang diberikan oleh guru. Hasil dari penerapan collaborative learning akan lebih efektif ketika siswa mampu menguasi lebih banyak kosakata bahasa Inggis. Kata Kunci: Teks anlytical exposition, kemampuan berbicara, collaborative learning. Abstract Teaching speaking is essential in EFL teaching learning. Speaking is categorized as productive skill. There is a system for thinking process in it. Speaking activity in EFL classroom has aim to use the knowledge that students have acquired for producing an oral text. Moreover, the use of learning speaking is that one is able to communicate with other through meaningful and receptive pattern. In this study, the researcher observes a teacher who uses collaborative learning in teaching speaking. The teacher creates an interesting way for speaking activity in which students are asked to present the topic that given by the teacher in front of classroom collaboratively. Many adavantages appear in this activity. This research is a descriptive qualitative research. The subjects are the teacher and the students of SMA Negeri 1 Sidoarjo in eleventh grade. The instruments, which are used in this research, are fieldnote, interview guideline, and the transciption of students performance. The implemeantation of collaborative learning in teaching speaking of analytical exposition text was successfully attract the students’ eager in speaking activity. The teacher are able to implement the method successfully. It is appropriate with the steps in the collaborative learning. The students’ give a good respond toward the implementation of collaborative learning. In establishing the result of the applicition of collaborative learning wheter it is good or not is not only by considering the students’ respond toward the implementation of the method. The students’ works are able to present the students’ comprehension toward the material given. The students’ ability in speaking analytical exposition was satisfy. The result would be better when the students could learn more vocabulary to support the result. Keywords: Collaborative learning, teaching speaking, analytical exposition. INTRODUCTION Speaking is one of four skills in language that should be mastered by someone when learning English. It is used by people to communicate each others. Therefore, it is important to master it. Besides that, English is one of the subjects which should be taught in education program in Indonesia. Moreover, it has become one of the subjects, which must be examined in National Examination of some school’s levels, Junior and Senior High School. In addition, it has an important role in developing people’s capability to communicate with others in today’s world (Cahyono, 2010). Therefore, it is important for students to master English. Richard (2008) points out that in speaking one tend to be getting something done, exploring ideas, working out some aspect of the world, or simply being together. In writing, it may be creating a record, committing events or moments to paper. Based on the definition above can be concluded that the purpose of speaking are to deliver, converse, or express ideas. The teacher has responsibility to make the students able to speak. However many students are reluctant to speak. Experiences have shown that students often lack of confidence and feared that classmates would make fun of them if they make mistakes or spoke incorrectly. Most of the students prefer to keep silent than express their opinion. Chou and Yen-Lin (2004) state that lack of speaking competence prohibits the opportunities for Asian students to interact with the instructor and peers in the ESL classroom. The characteristic of students in senior high school are expressive and like to gather and trust their friend. As a result the students like to tell everything to their friends. As a result the students are able to communicate well with society around them in their own mother tongue. Therefore, the students have no chance to practice English in their daily life. Therefore, students will find difficulty when they are asked to communicate in English. Considering the teaching speaking, the role of the teacher is important. Teacher should create an interesting activity to make the students motivated in learning speaking, especially for students in eleventh graders of senior high school. Students in eleventh grade of senior high school must be able to produce oral analytical exposition text. It is required in teaching learning process that is based on standar isi Bahasa Inggris 2006 the eleventh graders in the first semester in speaking skill that the eleventh graders of senior high school are expected having competence in responding a simple spoken text, in this case a simple analytical exposition text. Based on the research that has been done by Pattanpichet (2011) which is concern in investigating the effect of collaborative learning toenhance students’ speaking achievement, the researcher going to analyze the use of collaborative speaking in teaching speaking of analytical exposition. There are many kinds of activities that can help students in learning speaking. One of them is collaborative learning. Collaborative learning is a method in which the students work together on an assignment. These kinds of activities are expected to help students to build their self-confidence. By doing collaboration students will present about something with the partner. It makes them easier to work and easier to produce more words in their performance. Collaborative speaking also expected to make students more relax and confident with their performance. Students feel there is reinforcement in their performance because of the partner. Partner gives big influence in students’ performance. Moreover when student forget some words or one of part in the presentation the partner can remind and support the performance. Therefore their performance will be better. Lutters (2002) argues that collaborative learning encourages an iterative process of mutual understanding. Presentation in the workplace is rarely concluded with theatrical applause, but in contrast is routinely followed by active questions and answers from the “audience”. This kind of activity is expected to improve the students’ speaking ability in analytical exposition. Research done by Ulan (2011) has been proven that collaborative learning is an effective way in teaching speaking. Therefore, the writer will apply collaborative speaking in teaching speaking of analytical exposition. This study is expected to help students to perform and produce better spoken language of analytical exposition text. Moreover, it is expected that collaborative speaking will support each other performance and interaction. The students will be asked to present a topic in front of class in a pair. This activity is expected to improve their self-confidence and engage students in active classroom activity. Therefore, they can perform the best performance. Those explanataion aboe=ve lead the researcher to draw three research question in relation to the implementation of collaborative learning in teaching speaking of analytical exposition. The questions are as follow: How does the teacher implements collaborative learning n teaching speaking of analytical expositon? How is the students’ speaking ability after collaborative learning is implemented in teaching speaking of analytical exposition? How do the students’ respond toward the implementation of collaborative learning in teaching speaking of analytical exposition? METHOD Based on the research question and the objective of the study, the researcher used descriptive qualitative. Descriptive research studies are designed to obtain the information concerning the status of phenomena (ary, et al. 1985:322). The aim of this study is to describe a natural situation without giving manipulation or special treatment to the subject of the research. another expert, named Sukmadinata (2006:18) stated that descriptive research is a research which aims to describe a situation or natural phenomenon and it is done without manipulation or giving special attention to the subject of the research because all of events or activities grow nature. This research is design in word. It observe the process of implementation the collaborative learning in teaching speaking of analytical exposition and also the students’ speaking ability, and the students respond. The researcher uses descriptive qualitative as the research design based on two reasons, which are the objective of this study is to describe the implementation of collaborative learning in teaching speaking of analytical exposition. The subject of the study were the eleventh graders of SMA Negeri 1 Sidoarjo. The reason why the researcher chooses the eleventh grade students because analytical exposition text is one of the essential lesson in the first semester for those senior high school students. She wants to know how to make the students easily to understand the material without make the students bored. In this study, the researcher was collecting the data through observation, because the writer going to investigate the process of collaborative laerning activity in teaching speaking of analytical exposition directly in the classroom. The writer become an observer or non-participator and she uses the fieldnote to take a note about the activity that occur during teaching an dlearning process. Therefore, the reseracher can gather valuable information to complete this research. Then, the writer make a list of questions to interview the teacher who will implements the technique. And last, the writer also make some documentations such as the result of study during teaching learning process. According to Ary et.al (2010) states that three are three kinds of data collection in qualitative reasearch. They are observation, interview and document. In this case the researcher uses observation and interview as the technique to collect the data. Observation was used to gather information about the process in how the teacher implement the collaborative learning in teaching speaking of analytical exposition. Moreover, the collect information about the students achievement the reseacrher uses document that is recorder of student’ performance. The last, in gathering information about the students’ respond toward the implementation of collaborative learning in teaching speaking of analyticla exposition the researcher uses interview. In accomplising this research, the researcher uses feild note, interview guideline, and recorder as the instruments of this research. After all of data was collected, the researcher than arrange the data in to three part to analyze the data. According to Ary at.al (2010) there are three steps in the process of data anlysis in qualitative reserach. Theay are organizing and familiarizing, coding and reducing, and interpretating and representing. The first steps the reseracher familiarizing and organizing the valuable data. Then, the researcher give code in ecah valuable data and reduce it. The last, the reseacrher draw a conclusion to intrpretate and represent the research. RESULT AND DISCUSSION This chapter presents the result and discussion of the study as the answers for the research questions regarding to the implementation of collaborative learning in teaching speaking f analytical exposition, the students’ spekaing ability wafter the collaborative learning is implemented, the last is regarding to the students’ respond toward the implementation of collabortive learning in teaching speking of analytical exposition. The Implementation of Collaborative Learning in Teaching Speaking of Analytical Exposition In completing the research, the researcher conduted observation in SMA Negeri 1 Siodarjo was in three meetings. During conducting research, the writer made a list of the implementation of collaborative learning, students’ speaking ability, and students respond. The result was based on the three research questions. As a result, the implementation of collaborative learning in teaching speaking analytical exposition text had some points that could be compared further. The points were dealing with the topic, the method and the teaching learning process in SMA Negeri 1 Sidoarjo High School. The topic here refers to the material given in the class. The topic was about speaking analytical exposition text. It was suitable with the curriculum standard, because in that school analytical exposition text begin to be taught in eleventh grade. Furthermore, the topic was also understandable and could lead students to be an active speaker. Even though they faced some difficulties in those activity, they were still enthusiastic to express their own idea. The method here refers to the implementation of collabortaive learning in teaching speaking of analytical exposition. Since the teacher and students could implement those activity in teaching learning process, it means that this method was applicable. The students were participated actively in the class because the method encouraged them to share their opinions in the group work or individually. The researcher divided the discussion in to three parts. They are the implementation of collaborative learning in teaching speaking of analytical exposition and the second is the students’ speaking ability toward the implementation of collaborative learning, and the students’ respond to the implementation of collaborative learning in teaching speaking of analytical exposition. According to the brown (2004) speaking is a productive skill that can be directly and empirically observed, those observations are invariably colored by the accuracy and effectiveness of a test-takers listening skill, which necessarily compromises the reliability and validity of an oral production test. Moreover, Brown (2004) stated that one kind of speaking is Extensive oral production tasks include speeches, oral presentations, and storytelling, during which the opportunity for oral interaction from listeners is either highly limited or ruled out altogether. In this case the researcher highlight the term of oral production task include speeches, oral presentation and ruled out together. For that statement the researcher can conclude that there is a correlation between collaborative learning and speaking skill. Presentation belongs to part of speaking that the goal is ruled out together. The statement also supported by Ellis (2001) points out that the philosophy behind the subject was that of building a collaborative learning environment with the students finding information themselves, evaluating and critically analyzing the information. This condition makes them more creative and enjoys following the teaching learning process in the classroom, discussing it with one another, building structured arguments and drawing conclusions about the various topics under discussion. Therefore, collaborative learning can help students to be more active and creative. It can be concluded that collaborative learning can be used to teach speaking. Based on the result of observation, the researcher could conclude that the implementation of collaborative learning in teaching speaking of analytical exposition was implemented successfully. Relating to the steps of collaborative learning the teacher did the steps in collaborative learning. The first meeting the teacher asked the students to write down their own opinion about the topic that given by the teacher. in ths case the teacher was done the first stpe in collaborative learning. It is activate the students opinion as a brainstorming activity. The second, the teachers gave a text to the students and asked the students to find out the main idea of each paragraph in pair then discussed it with the classroom. According to the step of collaborative learning, it refers to the second stage of collaborative learning. The students work collaborative in small group. The last activity the teacher asked the students to present a presentation. In this case the students who became the audience are asked to ask or give coment toward the other group prsentation. This activity refers to the thrid stage of collaborative learning as stated by Lai (2011). He states that the third stage of collaborative learning when the students work individually on a similar assigment task. each students evaluating and critiquing others group performance. Therefore, it can be concluded that the teacher activity in teaching and learning process has similarity toward the collaborative learning stage. The Analysis of Students’ Works The second point is related to the students achievement, The researcher analyzed the students’ individual speaking ability based on the ESL speaking proficiency adapted from Haris (1969). The components of ESL speaking proficiency are pronunciation, fluency, vocabulary, comprehension and grammar. The result of the analysis showed that for pronounciation aspect. Most of students’ pronunciation problem necessitate concentrated listening and occasionally lead to misunderstanding. While others students’ pronounciation was always intelligible, though one is conscious a definite accent. Furthermore, the rest of the students’ pronounciation Has few trace of foreign accent. The next aspect of students’ speking ability is fluency aspect. It focused on the speed of speech that used by the students in explaining or presenting their topic in front of classroom. The result of the analysis showed that among 30 students, most of students’ fluency is that their speed and fluency are rather strongly, affected by language limitations. It was turned out when the students were trying to find the vocabulary of certain word they often used ‘e’ or silent in a second. While others students’ fluency showed that their speed or speech seems to be slightly affected by language problems. The students seemed interference with their native language. The rest of the students’ fluency aspect showed that their speech as fluent and effortless as that of native speaker. The next aspect is the vocabulary aspect of students’ performance. In this part, the analysis is focused on the word choice. It was important since the errors of it could result the change of meaning. The result of the analysis showed that among 30 students, most of students vocabulary aspect is that sometimes the students use inappropriate terms and/or must rephrase ideas because of lexical of inadequacies. Then several students vocabulary aspect was that they frequently used the wrong word: conversation somewhat limited because of inadequate vocabulary. The rest of students vocabulary aspect they used of vocabulary and idioms is virtually that native speaker. The next aspect that analyzed was the comprehension of students’ performance or presentation. In this part, the analysis focused on the content of the topic that presented by the students. The result of the analysis showed that among 30 students, most of students understood nearly everything at normal speed, although occasionally repetition may be necessary. When the students presented their presentation they oftenly repeated certain word or said’what I mean is...’. Several students understood most of what is said at slower-than-normal speed with repetition. The rest of students appeared to understand everything without difficulty.. The last aspect was the grammar aspect. The result of the analysis showed that among 30 students, most of students occasionally made grammatical and/ or word order errors that did not obscure meaning. The others students showed that they made frequent errors of grammar and word-order which occasionally obscure meaning. A few students made few (if any) noticeable errors of grammar or word order. Unfortunately, there was a student got this criteria grammar and word-meaning errors make comprehension difficult. Must often rephrase sentences and/ or restrict himself to basic pattern. The result above show that the students’ speaking ability was satisfy. This result is in hence to the statement by Nunan (2003) sataed that group work can be a quality time for the students to increase their opportunity to speak the target language during the lesson. In this case the students’ speaking ability were satisfy due to the teacher gives chance for the students to dominate the lesson. While the teacher only observed them and took their score. Therefore, the students achievement were satisfy. From the explanation above, it can be concluded that the implementation of collaborative learning in teaching speaking analytical exposition was successful. It could be turned out from the result of interview. The students said that it helped them in speaking. It also forced them to speak in front of class. The students were active in asking and answering section. They also get chance to practice their speaking skill. It is stated by Chou and Yen-Lin (2004) that lack of speking competence prohibit the opportunities for Asian students to interact eith the instructor and peers in the ESL classroom. In this case, when the teacher applied collaborative learning, in which the students are asked to make a presentation in group the stdents’ speaking ability were satisfy. It turns out that collaborative learning can be applied in teaching speaking. The Students’ Responses to the Implementation of Direct Reading Activity to Teach Reading Descriptive Texts From the result of interview, the researcher got information about the students’ respond to the implementation of collaborative learning in speaking of analytical exposition. The students agreed and supported that collaborative learning could be a method that applied in speaking class. The reason was the students got a chance to speak about a topic that there was no relationship to their lesson. Therefore, they should speak orally. They also stated that they are easier in delivering their ideas to become oral words. They were more confidence because they explained the topic together with their friend. It could support each other’s. The students also said that they more brave to speak in front of class. Collaborative learning is a good method to be implemented in speaking class. The teacher stated that the students were more active in speaking class. They could explain their topic well and more than she expected before. CONCLUSION AND SUGGESTION Conclusion The collaborative learning method can be implemented in teaching speaking of analytical exposition text to the eleventh graders of senior high school. The steps of the method are: Introducing the text. in the first meeting the teacher introduces analytical exposition text to the students. Explaining the definition of analytical exposition, explaining the goals, and explaining the generic structure of analytical exposition text. Regarding to the teaching and learning process toward the method, it is suitable. The teaching and learning activity match to the stage in collaborative learning. The first stage the teacher ask the students to deliver their own opinion about the topic that given by the teacher. then she askedd the students to discuss in pair about the assignment that given. The thrird stage, the teacher asks the students to present their presentation. In this case the students work individually to ctiqiue, comment, or ask questions toward the others group presentation. The students’ speaking ability toward the implementation of collaborative learning showed satisfaction result. The speaking components that adapted from Harris (1969) showed a satisfy result. Most of students’ pronunciation, fluency, vocabulary, comprehension, and grammar were satisfy. The students’ respond toward the implementation of collaborative learning in teaching speaking of analytical showed good respond. it showed by the students toward their performance they were active, motivated and enjoy during the teaching and learning process. Suggestions The result of this study was that the teacher was successfully implement the collaborative learning in teaching speaking of analytical exposition. In this case, the researcher suggests to teachers that she would be better to find or create interesting ways in teaching and learning process. For example, collaborative learning can be applied in classroom. Moreover, for the students who want to be better in English especially in speaking skills, they need to improve their vocabulary. By improving their vocabulary, the students will be better and easy to creat and share their opinion in English. REFERENCES Ary, D. a. (2010). Introduction to Research in Education 8th Edition. USA: Wadsworth Cengage Learning. Brown, H. D. (2004). Language Assessment Principles and Classroom Practices. California: Longman. Brown, H. D. (2000). Principles of Language Learning and Teaching. California: Longman. Chisholm, R. (1989). Using Collaborative Techniques in a Speech Class. Writing Across thc Curriculum,vol 1 , 104-112. Diaz, V., Brown, M., & Salmons, J. (2010). Learning Initiative. Educause , 1-4. Ellis, A. (2001). Students-Centered COllaborative Learning. Monash University: FLITE Centre. Harris, D. P. (1969). Testing English as Second Language. New Delhi: McgrowHill. Lai, E. R. (2011). Collaboration: A Literature Review. Pearson: Pearson. Littlewood, W. (2002). Communicative Language Teaching. Cambridge: Cambridge University Press. Lutters, W. G. (2002). Storytelling in Collaborative Work:Design Challenges for Capturing and Representing Sensitive Interactions. Baltimore: Department of Information Systems. Nunan, D. (2003). Practical English Language Teaching. McGraw-Hill Companies. Pattanpichet, F. (2011). The Effects Of Using Collaborative Learning To Enhance Students' English Speaking Achievement. Journal of College Teaching & Learning , 8, 1-10. Remedios, L. (2008). Framing Collaborative Behaviors: Listening and Speaking Problem-based Learning. Interdisciplinary Journal of Problem-based Learning, vol 2, no 1 , 1-20. Richards, J. C. (2008). Teaching Listening and Speaking From Theory to Practice. New York: Cambridge University Pers. Sudarwati, Th M; Eudia, Grace;. (2006). Look Ahed AN ENglish Course for Senior High School Students Year XI. Jakarta: Erlangga. The Principle of Teaching. (2011). Dipetik November Wednesday, 2013, dari feed:http://www.slideshare.net/rss/latest Van Boxtel, C., Van der Linden, J., & Kanselaar, G. (2000). Collaborative learning tasks and the elaboration of conceptual knowledge. Learning and Instruction, 10(4), 311–330.